Oblique bile duct predisposes to the recurrence of bile duct satones - Strnad, Pavel; Figura, Guido von; Gruss, Regina; Jareis, Katja-Marlen; Stiehl, Adolf; Kulaksiz, Hasan (PLOS ONE, 2013)
Background and Study Aims Bile stones represent a highly prevalent condition and abnormalities of the biliary tree predispose to stone recurrence due to development of biliary stasis. In our study, we assessed the importance of an altered bile duct course for stone formation. Patients and Methods 1,307 patients with choledocholithiasis in the absence of any associated hepatobiliary disease who underwent endoscopic retrograde cholangiopancreatography (ERCP) between 2002 and 2009 were analysed. The angle enclosed between the horizontal portion of the common bile duct (CBD) and the horizontal plane was measured (angle α). Oblique common bile duct (OCBD) was defined as a CBD with angle α<45°. Results 103 patients (7.9%) were found to harbour OCBD and these were compared to 104 randomly selected control subjects. Compared to controls, OCBD patients were (i) significantly older (72±13 vs. 67±13, p<0.00001); (ii) more frequently underwent a cholecystectomy (p = 0.02) and biliary surgery (p = 0.003) prior to the diagnosis and (iii) more often developed chronic pancreatitis (p = 0.04) as well as biliary fistulae (p = 0.03). Prior to and after ERCP, OCBD subjects displayed significantly elevated cholestatic parameters and angle α negatively correlated with common bile duct diameter (r = -0.29, p = 0.003). OCBD subjects more often required multiple back-to-back ERCP sessions to remove bile stones (p = 0.005) as well as more ERCPs later on due to recurrent stone formation (p<0.05). Conclusion OCBD defines a novel variant of the biliary tree, which is associated with chronic cholestasis, hampers an efficient stone removal and predisposes to recurrence of bile duct stones.